Low-cost circular LED dome lighting system for Insecta (Hexapoda) image capture in self-assembly stereomicroscope - Ferreira, André da Silva; Bravo, Freddy; Castro, Ivan (EntomoBrasilis, 2021)
The use of high-resolution images in studies of morphology, taxonomy and systematics has been increasingly frequent, especially in Insecta. However, suitable lighting systems are still very expensive and/or difficult to use. On the other hand, currently the use of 3D printers has helped to make lighting equipment more accessible for researchers to equip their laboratories. Here we present a low-cost circular LED dome lighting system for capturing scientific micro and macro photography on a self-assembly stereomicroscope. We also present the necessary components for making the dome, as well as the elements used to capture the photographs.